KOMPARASI PENILAIAN TINGKAT KESEHATAN BANK DITINJAU DARI GOOD CORPORATE GOVERNANCE (GCG) PADA PT.BANK RAKYAT INDONESIA (Persero) Tbk DAN PT.BANK TABUNGAN NEGARA Tbk - Sherlly Aprilliani; Andi Hasryningsih Asfar (Jurnal Bina Bangsa Ekonomika, 2021)
The health of a bank is the ability of a bank to conduct operational activities or assessment of a bank's financial statement conditions in a certain period in accordance with Bank Indonesia standards, simply the health of the bank is a bank that can carry out its functions properly and can maintain public trust. The purpose of this study is to find out the comparison of bank health level assessments reviewed from The Bank's Good Corporate Governance (GCG) in BRI and BTN in 2016-2018. The method used is comparative descriptive i.e. research that compares the presence of one or more variables on two or different samples, or at different times. The results of the study that GCG at PT Bank Rakyat Indonesia (Persero) Tbk and PT Bank Tabungan Negara (Persero) Tbk both  ranked  2nd and entered the  healthy category with a weight of 1.50><2.50 Composites in three consecutive years. The conclusion of the study that PT. Bank Rakyat Indonesia (Persero) Tbk  and  PT. Bank Tabungan Negara (Persero) tbk in the period 2016-2018 as a whole is in good condition